2014
DOI: 10.1088/0953-2048/28/2/024002
|View full text |Cite
|
Sign up to set email alerts
|

High pinning performance of YBa2Cu3O7−xfilms added with Y2O3nanoparticulate defects

Abstract: We report the epitaxial growth and superconducting properties of Y2O3-added YBa2Cu3Ox (YBCO) films grown on SrTiO3-buffered MgO substrates by pulsed-laser deposition using surface-modified YBCO targets. Areas of Y2O3 sectors on the YBCO target were increased to 5.44% and 9.22% of the total YBCO pellet in order to find a correlation between the Y2O3 content, morphology, and the pinning properties of YBCO+Y2O3 mixed films. The maximum global pinning forces, FP, at 77 K were 14.3 GN m−3 and 1.15 GN m−3 for the Y2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The presence of this lattice defect is highly desirable as it contributes to the pinning of the magnetic flux vortices and enhances the physical properties of YBCO. 37,[41][42][43][44][45][46][47] However, its structure and chemistry is complex, 1,48 as the system forms Cu and O vacancies buried within the very same intergrowth in order to balance the stoichiometry when an extra CuO x layer is inserted in the YBCO structure. Gazquez et al reported that the most favorable vacancy configuration was the one containing two Cu vacancies accompanied with three O vacancies (2V Cu + 3V O ), with one O vacancy located in the upper CuO chain and two in the lower one, 1 as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this lattice defect is highly desirable as it contributes to the pinning of the magnetic flux vortices and enhances the physical properties of YBCO. 37,[41][42][43][44][45][46][47] However, its structure and chemistry is complex, 1,48 as the system forms Cu and O vacancies buried within the very same intergrowth in order to balance the stoichiometry when an extra CuO x layer is inserted in the YBCO structure. Gazquez et al reported that the most favorable vacancy configuration was the one containing two Cu vacancies accompanied with three O vacancies (2V Cu + 3V O ), with one O vacancy located in the upper CuO chain and two in the lower one, 1 as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Incoherent fine NP in MOD films Part of the successful addition of NPs in MOD can be found in Figure 3 by comparing the structural and superconducting properties for inclusions with coherent and incoherent interfaces, that is, coherent NRs in films grown using a low-temperature growth technique via PLD (PLD-BHO-NRs), 20 coherent nanoparticles (PLD-Y 2 O 3 -NPs) 38 and incoherent nanoparticles (MOD-BHO-NPs (d coat = 30 nm)). For both PLD films, the c-axis length of the superconducting matrix lattice expands markedly with increasing vol.% but, in contrast, remains flat for MOD-BHO-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating self-assembled inclusions into high-temperature superconductors has been established as a very efficient route to enhance their critical currents. Depending on the fabrication process, these inclusions may be prepared in the form of almost spherical particles [1][2][3][4][5][6][7][8][9][10], nanorods [11,12], or combinations thereof [13,14]. This technology is implemented in today's second-generation superconducting wires based on rare-earth barium copper oxide (REBa 2 Cu 3 O 7 or RE-BCO) coated conductors [15,16], where the rare earth (RE) is mostly yttrium (Y) or gadolinium (Gd).…”
Section: Introductionmentioning
confidence: 99%